Hypertensive Patients’ Knowledge of Risk Factors and Warning Signs of Stroke at Felege Hiwot Referral Hospital, Northwest Ethiopia: A Cross-Sectional Study - Addisu Taye Abate; Netsanet Bayu; Tesfamichael G. Mariam (Neurology Research International)
Background. Stroke is a neurological condition which is a major cause of death and disability in many low- and middle-income countries. However, several modifiable risk factors are becoming significant. Hypertension is the most common stroke risk factor globally as well as in our country, Ethiopia. Objective. The aim of this study was to assess hypertensive patients’ knowledge of risk factors and warning signs of stroke at Felege Hiwot Referral Hospital, Northwest Ethiopia, 2018. Method. An institutional based cross-sectional study design was conducted in May 01–30/2018. A total of 278 hypertensive patients were enrolled and systemic random sampling technique was employed to select the study participants. Data was collected through an interviewer-administered questionnaire. The collected data was entered into Epi info 7 and exported to SPSS version 22 for analysis. Binary and multivariable logistic regressions were used and P value ≤ 0.05 was considered as statistically significant. Result. Out of the total 284 selected hypertensive patients, 278 of them responded completely with a response rate of 97.9 %. Of these, more than three fourths, 214 (77%) and 201 (72.3%), of them did not identify any risk factors and warning signs of stroke, respectively, with an overall proportion of only 18.3% of them having good knowledge towards stroke. Risk factor of stroke most commonly known to the respondents was physical inactivity (21.58%), whereas hypertension was the least described risk factor (3.6%). Regarding stroke warning signs, sudden weakness on one side of the body (35.97%) was the most commonly known warning sign of stroke to the respondents. Being able to read and write, being young, urban residence, and having sufficient monthly income were significantly associated with the overall knowledge of hypertensive patients towards stroke. These findings suggest the need for emphasizing on stroke education regarding its risk factors and warning signs through public or social media and health education targeting to low-income high risk subjects.